OC-043 Nfkb1 deficiency alters susceptibility to helicobacter spp. induced il-1Β secretion in bone marrow derived dendritic cells. (22nd June 2015) - Tang, JM; Pritchard, DM; Duckworth, CA; Caamano, J; Burkitt, MD
Abstract : Introduction: Deletion of specific NF-κB subunits in mice alters the outcome of Helicobacter felis infection. Nfkb1 -/- mice developed more severe gastric atrophy than wild-type (WT) mice 6 weeks after H. felis infection, whereas Nfkb2 -/- mice were protected from this pathology. The mechanisms underlying these outcomes remain unclear, but gastric Il1b transcript abundance was increased in H. felis infected Nfkb1 -/- mice relative to WT, and polymorphisms at the IL1B locus have also been associated with gastric cancer in humans. Il1b transcription is regulated by classical pathway NF-κB signalling. IL-1β secretion also requires the formation of inflammasome complexes, which form following intracellular pathogen recognition, and lead to the autocatalysis of pro-caspase 1 and subsequent cleavage of IL-1β. We hypothesised that inflammasome signalling was altered in mice with abrogated NF-κB signalling and that this influenced H. felis induced pathology. We therefore investigated inflammasome mediated signalling in bone marrow derived dendritic cells (BMDCs) from mice lacking specific NF-κB subunits. Method: Cells were harvested from C57BL/6, Nfkb1 -/-, Nfkb2 -/- and c-Rel -/- bone marrow. Dendritic cells were differentiation using 20 ng/ml GM-CSF for 7 days. BMDCs and WT derived gastric epithelial organoids were primed with 20 ng/ml LPS and exposed to 300 μg/ml silica, 5 mM ATP, H. pylori (ATCC 53726) or H. felis (ATCC 49179) (MOI 1:100) with or without a pan-caspase inhibitor (Z-VAD-fmk), an inhibitor of NADPH oxidase (APDC) or 50 mM KCl. Secreted IL-1β and TNF concentrations were measured by ELISA. Results: LPS alone induced TNF, but not Il-1β, secretion in all genotypes of BMDCs. Both silica and ATP induced IL-1β secretion in WT BMDCs pre-stimulated with LPS (750 ± 65 and 530 ± 77 pg/ml). BMDCs derived from NF-κB deficient mice secreted similar amounts of Il-1β in response to these stimuli. Inflammasome inhibitors returned IL-1β secretion to unstimulated levels. Gastric epithelial organoid cultures treated with LPS and silica did not secrete either IL-1β or TNF. Following exposure to H. felis or H. pylori, Nfkb1 -/- BMDCs, but not other genotypes, exhibited a 2.6 fold increase in IL-1β secretion compared to untreated cells or cells stimulated with LPS. This was abrogated by Z-VAD-fmk. Conclusion: These data identify potent inflammasome activation in NF-κB deficient BMDCs. H. pylori and H. felis also weakly stimulated inflammasome activation in NFkb1-/- BMDCs. This mechanism may contribute to the more severe gastric phenotype that is observed in NFkb1 -/- mice in vivo following H. felis infection. Further studies are required to identify how NF-κB1 deletion influences inflammasome formation, and whether altered IL-1β transcription is involved. Disclosure of interest: None Declared.